The Missing Piece in Performance Development - Kinley, Nik; Ben-Hur, Shlomo (MIT Sloan Management Review, 2017)
In recent years, organizations have begun to prioritize processes for improving future performance over evaluating employees' past efforts. Yearly development objectives and annual reviews are being replaced by real-time feedback delivered directly by line managers. Although this shift holds much promise, it risks bumping up against some hard realities - namely, the ability of line managers to help employees develop. In reality, many managers aren't confident they can change employee behavior.